Archaea: Underestimated Domain in Pharmaceutical Quality Control - Eissa, Mostafa (Kathmandu University Journal of Science, Engineering and Technology, 2018)
Quality control monitoring of microbiological attribute of the pharmaceutical environment - including pharmaceutical water and compressed gases- and products is an essential prerequisite to judge the goodness of the manufacturing environment and safe release of the pharmaceutical article into the market, respectively. While most of the quality control tests mainly focus on detection and/or enumeration of both bacteria and fungi, Archaea were not considered on regular testing despite the fact that they are widely distributed in nature and found in human body. Conventional culture techniques in laboratories are not suitable for most members of Archaea. The ever-growing number of patients with a defective immune system - accompanied by increasing list of objectionable microbes - highlights the potential risk that may emerge from underestimating other non-culturable microorganisms on traditional microbiological media even if it has not shown any signs of pathogenesis till now. The pharmaceutical technology should overcome this barrier to guard against any possible outbreaks provisionally that may emerge from creeping microbes undetected to the body of patients in addition to the possible spoiling of pharmaceutical products, especially those with significant water activity. Kathmandu University Journal of Science, Engineering and Technology Vol. 13, No. 2, 2017, page: 98-102